Development of High-current DC Breaker Based on IGBT Used in the Heating Process of Tantalum - XU Peng; CHEN Yan; WAN Chaoqun; FENG Qin (Kongzhi Yu Xinxi Jishu)
In the application of X-ray production by bremsstrahlung diode, controllable stable DC is required for heating the anode material—Tantalum. The current coming from high capability low-voltage battery must be more than 2 kA. A kind of high-current DC breaker based on IGBT was developed. This breaker is used to control the discharging and supply stable DC for heating Tantalum. It changes IGBT turn-off speed by gate drivers, decreases the over-voltage caused by stray inductance. The field testing results indicates that these indicators such as the sustainable DC, the current turn-off capability, and the sustainable time of on-state can fully meet the requirements of this device.